Effects of the Teams Games Tournament (TGT) Learning Model Assisted by Spinning Wheel Media on Students’ Learning Outcomes in Atomic Structure - Lita Lokollo; Yeslia Utubira (Universitas Negeri Gorontalo, 2026)
Atomic structure material is abstract and requires a strong conceptual understanding, so innovative learning models and media that actively engage students are needed. This study seeks to investigate the impact of the Teams Games Tournament (TGT) learning model, supported by spinning wheel media, on the learning outcomes of Grade X high school students in atomic structure. The study employed a quantitative approach using a quasi-experimental method with a pretest–posttest control group design. The research sample consisted of two classes, namely class X1 as the control class and X7 as the experimental class, each comprising 27 students. The collected data were analyzed using descriptive and inferential statistical techniques with SPSS. Analysis using the Mann–Whitney U test indicated a significance level of 0.046 (p < 0.05), confirming that the learning outcomes differed significantly between the experimental and control groups. Students in the experimental class, where the TGT model supported by spinning wheel media was applied, achieved higher learning outcomes compared to those in the control class using traditional teaching methods. Therefore, it can be determined that the Teams Games Tournament learning model supported by spinning wheel media results in a significant improvement in students’ learning outcomes in atomic structure and can serve as an innovative alternative in high school chemistry learning.